Behavioral skills training to increase interview skills of adolescent males in a juvenile residential treatment facility. Issue 4 (17th April 2020) - Edgemon, Anna Kate; Rapp, John T.; Brogan, Kristen M.; Richling, Sarah M.; Hamrick, Sally A.; Peters, Rachel J.; O'Rourke, Soracha A.
Abstract : Some studies suggest that acquiring employment following release from prison may reduce recidivism; however, few studies have evaluated procedures for teaching job‐related skills to adolescents in residential detention facilities. Stocco et al. (2017) used behavioral skills training (BST) to improve interview skills of college students. The current study used a nonconcurrent multiple baseline design across participants to evaluate the extent to which BST improved interview skills for 7 adolescents who had been adjudicated for sexual offenses. Results show that BST increased appropriate responses to interview questions for 4 students and BST plus modifications (i.e., stimulus and response prompts) increased correct responding to questions for the other 3. In addition, BST increased appropriate questions, correct posture, and smiling, and decreased fidgeting for all 7 students. We briefly discuss the social implications of teaching interview skills to adjudicated adolescents, as well as the limitations of the findings.